Catering for large numbers of tourists: the McDonaldization of casual dining in Kruger National Park - Ferreira Sanette L.A.; W. Van Zyl Gesina (Bulletin of Geography. Socio-Economic Series)
Since 2002 Kruger National Park (KNP) has subjected to a commercialisation strategy. Regarding income generation, SANParks (1) sees KNP as the goose that lays the golden eggs. As part of SANParks’ commercialisation strategy and in response to providing services that are efficient, predictable and calculable for a large number of tourists, SANParks has allowed well-known branded restaurants to be established in certain rest camps in KNP. This innovation has raised a range of different concerns and opinions among the public. This paper investigates the what and the where of casual dining experiences in KNP; describes how the catering services have evolved over the last 70 years; and evaluates current visitor perceptions of the introduction of franchised restaurants in the park. The main research instrument was a questionnaire survey. Survey findings confirmed that restaurant managers, park managers and visitors recognise franchised restaurants as positive contributors to the unique KNP experience. Park managers appraised the franchised restaurants as mechanisms for funding conservation.